Dinosaurs fight to survive : mysterious death and discovery in outback Queensland - Siva, Rose (Salisbury, Qld. : Boolarong Press, 2016)
"A dinosaur dig in far west Queensland unearths a mystery – how did two vastly different dinosaurs end up in the same pre-historic grave? Follow the story of Matilda the sauropod and Banjo the theropod, their chance meeting, and the final mystery is revealed. Bones of Matilda and Banjo have been found by 'diggers' on dinosaur digs and are now on display at the Australian Age of Dinosaurs at Winton." --Back cover.
For primary school age.
Keywords: Dinosaurs -- Juvenile fiction; Dinosaurs -- Queensland -- Juvenile fiction; Queensland -- Juvenile fiction; Australian